The Effect of Exercises for the Smart Jacket Device (Smart Jacket) According to some Biokinematic Variables and Improving the Level of Accuracy of the Skill Performance of the May Giry Kick in Youth Karate - Neamah, Ali; Wahed, Bashaer; Abbas, Ahmed (Pubmedia Jurnal Pendidikan Olahraga, 2024)
The study aimed to design and manufacture the smart jacket to improve some bio kinematic variables and improve the level of skill performance of the May Giry kick in karate. One of the hypotheses of the research is that the exercises for the smart jacket device have a significant impact on some bio kinematic variables and improve the level of skill performance of the May Giry kick in karate for young people. The researcher used the experimental approach by designing the experimental and control groups and the method of pre- and post-measurement for its suitability to the nature of the research, the study was conducted on a sample of the youth forum players at the age of (17-19) years in karate, and the number of (20) players, and the sample was selected randomly. The most important conclusions were that the exercises prepared by the coach and the exercises with the proposed device have a positive impact on the kick of May Giry in karate. The researchers also recommend circulating the device to clubs in the province and the country to be used as an auxiliary training device and to be included in the trainings.